Odpowiedź:
zad 1
w(x)=-3x²-5x³+x+8
u(x)=[tex]x^{5}[/tex]-5x³-4x+8
w(x)-2*u(x)=-3x²-5x³+x+8-2*([tex]x^{5}[/tex]-5x³-4x+8)=
-3x²-5x³+x+8-2[tex]x^{5}[/tex]+10x³+8x-16=
-2[tex]x^{5}[/tex]+5x³-3x²+9x-8
zad 2
(4x²+1)(1-x²)(6-3x)=
(4x²-4[tex]x^{4}[/tex]+1-x²)(6-3x)=
24x²-12x³-24[tex]x^{4}[/tex]+12[tex]x^{5}[/tex]+6-3x-6x²+3x³=
12[tex]x^{5}[/tex]-12[tex]x^{4}[/tex]-9x³+18x²-3x+6
zad 3
[tex]-x^{4}+5x^{3}-4x-10=-(-2)^{4}+5*(-2)^{3}-4*(-2)-10=[/tex]
[tex]-16+5*(-8)+8-10=[/tex]
[tex]-16-40-2=-58[/tex]
Szczegółowe wyjaśnienie: